Eleatic Ontology in Aristotle: Introduction - David Bronstein; Fabián Mié (My University, 2021)
The introduction summarizes the six new papers collected in Volume 1, Tome 5: Eleatic Ontology and Aristotle. The papers take a fresh look at virtually every aspect of Aristotle’s engagement with Eleaticism. They are particularly concerned with Aristotle’s responses to Parmenidean monism, the Eleatic rejection of change, and Zeno’s paradoxes. The contributions also focus on the ways in which Aristotle developed several of his own theories in metaphysics and natural science partly in reaction to Eleatic puzzles and arguments.
Keywords: Eleaticism; Aristotle; Parmenides; Zeno; Ontology; Monism; Motion; Time; Magnitude; Infinity